Review of Dynamic Decision Making ForConnected VehiclesIn IotSystem - Miss. Sonal Sanjay Ayare; Dr. Suraj V. Pote; Dr. Jaydeep B. Patil (Journal for ReAttach Therapy and Developmental Diversities, 2023)
By leveraging real-time data and sophisticated algorithms, dynamic decision-making for connected vehicles elevates safety and efficiency to the level of a paradigm shift in transportation technology. This article examines the present state of dynamic decision-making, emphasizing the possible advantages and difficulties it may present. The utilisation of critical elements including data analytics, machine learning, and artificial intelligence empowers interconnected vehicles to accurately and promptly traverse intricate surroundings. However, widespread adoption is hindered by infrastructure integration, cybersecurity vulnerabilities, and public acceptability, all of which pose substantial obstacles. The prospective advantages, such as decreased accidents, alleviated traffic congestion, and enhanced mobility, emphasize the criticality of confronting these obstacles. In the future, the potential for dynamic decision-making in connected vehicles is contingent upon connectivity advancements, including the integration of autonomous features and 5G technology. These advancements hold the potential to revolutionize transport within smart cities by streamlining traffic circulation and delivering customized experiences. Sustained investigation, stakeholder collaboration, and the establishment of regulatory frameworks are imperative in order to fully harness the capabilities of dynamic decision-making in connected vehicles.